2012
DOI: 10.5897/ajbm11.2528
|View full text |Cite
|
Sign up to set email alerts
|

Quality public services dimensions model as a basis for better customer satisfaction management

Abstract: In the paper, the importance of quality public services dimensions for achieving higher customer satisfaction is presented and explored on the example of Slovenian administrative units. Purpose of the research was to identify which quality dimensions are the most relevant for quality service delivery in Slovene administrative units in order to contribute to strengthening their customer satisfaction management. Survey questionnaire was developed to gather the research data and as the research methodology, struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Another category of the questionnaire, customer service in public transportation, was based on the research by Lai and Chen (2011) and Carreira et al (2014), who emphasized the importance for each frontline service provider, i. e., drivers and ticket inspectors, to be professional as well as civilized and polite when interacting with the passengers. According to Manzin et al (2012), adequate equipment and its technical condition, ticketing and activation system, physical safety of passengers, comfortable public transport vehicles, cleanliness and environmentally friendly transport are several of the factors that have great influence on the satisfaction with the public transport services; therefore, they provided the basis for the category quality of public transport equipment. Mahmoud and Hine (2016) claimed that in order to provide great quality public services and to gain customer satisfaction, peculiarities of each customer, the needs of disabled people who want to use public transport, the needs of parents with young children, or people with pets or bicycles and other modes of transport must to be taken into account; therefore, the category accommodation of different consumer groups in public transport was also included.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another category of the questionnaire, customer service in public transportation, was based on the research by Lai and Chen (2011) and Carreira et al (2014), who emphasized the importance for each frontline service provider, i. e., drivers and ticket inspectors, to be professional as well as civilized and polite when interacting with the passengers. According to Manzin et al (2012), adequate equipment and its technical condition, ticketing and activation system, physical safety of passengers, comfortable public transport vehicles, cleanliness and environmentally friendly transport are several of the factors that have great influence on the satisfaction with the public transport services; therefore, they provided the basis for the category quality of public transport equipment. Mahmoud and Hine (2016) claimed that in order to provide great quality public services and to gain customer satisfaction, peculiarities of each customer, the needs of disabled people who want to use public transport, the needs of parents with young children, or people with pets or bicycles and other modes of transport must to be taken into account; therefore, the category accommodation of different consumer groups in public transport was also included.…”
Section: Methodsmentioning
confidence: 99%
“…Vilkaitė-Vaitonė et al (2016) mentioned that consumer satisfaction research helps identify key determinants of consumer dissatisfaction with the services of an organization, and after each is assessed, appropriate measures can be selected and all efforts can be focused on eliminating the factors which cause dissatisfaction. Research on consumer satisfaction with public services revealed not only consumers' opinions about certain services but also their needs, desires, and expectations (Manzin et al, 2012;Diržytė & Patapas, 2013;Patapas & Žilionytė, 2016).…”
Section: The Analysis Of Consumer Satisfaction With Public Transport Servicesmentioning
confidence: 99%